STAGES OF DEVELOPING METHODOLOGICAL TRAINING OF FUTURE MUSIC TEACHERS BASED ON TEACHING THE UZBEKISTAN FOLK LOCAL MUSIC STYLES MODULE (World Bulletin of Social Sciences, 2025)
In our country, the upbringing of a spiritually mature person has been elevated to the level of a state task. Large-scale work is being carried out in this regard on the basis of state programs. The active participation of artists in the spiritual and educational reforms of our independent state and the upbringing of young people as a loyal and harmonious generation are of great importance. In the upbringing of such spiritually mature people, the role of "Music Culture" classes in secondary schools and extracurricular art circles is incomparable. In order to raise the activities of music and amateur art circles in our republic to a higher level, it is important to have a high-quality teaching method